Cricket meal as an alternative to fishmeal in diets for african catfish (Clarias gariepinus) / Norhidayah Mohd Taufek - Norhidayah , Mohd Taufek (2016)
In Malaysia, extensive farming of African catfish over the past decades has increased the utilization of fishmeal as the preferred aquafeeds owing to its highly nutritional properties. However, various pressures have been put on the fish farming industry to switch to more sustainable diet in order to reduce the dependency on fishmeal as the sole fish feed. Therefore, the aim of this thesis was to evaluate the potential of cricket in diets for African catfish in terms of growth performance, nutrient and amino acids digestibility, immunostimulant properties and susceptibility to oxidative stress. Four feeding trials were conducted to determine the use of cricket meal in African catfish diet. Cricket meal was capable of serving as an alternative protein replacement for fishmeal in the diet of farmed African catfish up to 100% without negatively affecting body composition and feed utilisation. Besides, fish fed cricket meal exhibited significantly higher nutrient and amino acids digestibility than fishmeal-fed fish. Mortalities at 12 days post-challenge with Aeromonas hydrophila was significantly decreased at dietary of 35% and 40% crude protein (CP) compared to control (fishmeal diet). From the pathogenic test, Aeromonas hydrophila isolation shows the highest count in the intestine of the control group while the lowest in the liver of the fish fed with 35% CP diet suggesting that dietary cricket meal enhanced the innate immune system and survivability of African catfish. Antioxidant activity of catalase was higher in 100% cricket meal substitution with 35% CP compared with fish fed other diets while glutathione S-transferase (GST) and superoxide dismutase (SOD) showed an increasing trend with higher incorporation of cricket meal although no significant difference was observed between all diets. These results signify that cricket meal could be a potential alternative for fishmeal as a protein source in African catfish diet without having any adverse health effect while at the same time improving growth and feed efficiency.